2012
DOI: 10.1105/tpc.112.102855
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Uncovers Regulation of Long Intergenic Noncoding RNAs in Arabidopsis

Abstract: Long intergenic noncoding RNAs (lincRNAs) transcribed from intergenic regions of yeast and animal genomes play important roles in key biological processes. Yet, plant lincRNAs remain poorly characterized and how lincRNA biogenesis is regulated is unclear. Using a reproducibility-based bioinformatics strategy to analyze 200 Arabidopsis thaliana transcriptome data sets, we identified 13,230 intergenic transcripts of which 6480 can be classified as lincRNAs. Expression of 2708 lincRNAs was detected by RNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
733
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(813 citation statements)
references
References 75 publications
53
733
1
5
Order By: Relevance
“…Furthermore, we demonstrated that AtGUT15 is capped and undergoes alternative splicing. The same mRNA-like features have also been observed in mammalian and other plant lncRNAs [4, 6, 24]. …”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, we demonstrated that AtGUT15 is capped and undergoes alternative splicing. The same mRNA-like features have also been observed in mammalian and other plant lncRNAs [4, 6, 24]. …”
Section: Discussionsupporting
confidence: 62%
“…Some of these molecules function in chromatin modification or as miRNA mimics, whereas others are involved in ribosome biogenesis [i.e., small nucleolar RNAs (snoRNAs)]. Here, we used existing compendia of ncRNAs (49,50) to seek ones that may be ribosome-associated. First, we identified ncRNAs with mRNA-seq reads (>5 rpkM) in both normoxic and hypoxic samples.…”
Section: Hypoxia Reduces Ribosome Protection Associated With Initiatimentioning
confidence: 99%
“…Plants produce over 30,000 putative noncoding RNAs (ncRNAs) that are 5′-capped and 3′-polyadenylated (48,49). These include natural antisense transcripts (NATs), long intergenic/intronic ncRNAs (lincRNAs), and RNAs encoding ORFs of only 30-100 amino acids [small ORFs (sORFs)] (50).…”
Section: Hypoxia Reduces Ribosome Protection Associated With Initiatimentioning
confidence: 99%
“…Thousands of lincRNAs are found in mouse (Guttman et al, 2009(Guttman et al, , 2010Liu et al, 2011;Luo et al, 2013;Sigova et al, 2013), human (Cabili et al, 2011;Hangauer et al, 2013;Sigova et al, 2013), chimpanzee (Wetterbom et al, 2010), zebrafish (Pauli et al, 2012;Ulitsky et al, 2011), frog (Tan et al, 2013), nematode (Nam and Bartel, 2012) and Arabidopsis (Liu et al, 2012). Some newly identified lincRNAs have well-validated functions.…”
Section: Introductionmentioning
confidence: 99%